2015
DOI: 10.3390/aerospace2010001
|View full text |Cite
|
Sign up to set email alerts
|

Shock Wave Diffraction Phenomena around Slotted Splitters

Abstract: In the field of aerospace engineering, the study of the characteristics of vortical flows and their unsteady phenomena finds numerous engineering applications related to improvements in the design of tip devices, enhancement of combustor performance, and control of noise generation. A large amount of work has been carried out in the analysis of the shock wave diffraction around conventional geometries such as sharp and rounded corners, but the employment of splitters with lateral variation has hardly attracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Gnani et al 11 employed splitters with a spike-shaped structure to produce shock diffraction and visualized the shock and turbulence phenomena using schlieren photography. They observed that the reflected shock waves were distorted during the process of passing through the vortex, but remained continuous and were not cut off by the vortex.…”
Section: A Backgroundmentioning
confidence: 99%
“…Gnani et al 11 employed splitters with a spike-shaped structure to produce shock diffraction and visualized the shock and turbulence phenomena using schlieren photography. They observed that the reflected shock waves were distorted during the process of passing through the vortex, but remained continuous and were not cut off by the vortex.…”
Section: A Backgroundmentioning
confidence: 99%
“…It is recognized that the optical flow visualization is the most suitable method to observe the shock structures in the compressible flow. Authors in [31] qualitatively investigated and experimentally visualized the shock wave diffraction phenomena around two splitters with spike-shaped structures for different Mach numbers. Schlieren photography was used to obtain an insight into the sequential diffraction processes that take place in different planes and as a result, a complete description of the main flow features was successfully provided.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The whole gas flow was imaged using a spherical mirror with focal length of 2000 mm and diameter of 300 mm. Furthermore, for detailed images including the intermittent shock structures (Mach disks), a smaller spherical mirror with focal length of 650 mm and diameter of 63 mm was used [23,[31][32][33].…”
Section: Experimental Set-upmentioning
confidence: 99%
“…In this regard, a comprehensive review of various methods to attenuate shock/blast waves was reported by Igra et al [ 2 ] addressing both experimental and numerical approaches. Essentially, shock-wave attenuation by geometrical means such as rigid barriers or sudden changes in the flow geometries is governed by compression, rarefaction regions arising from shock diffraction and intense shock-turbulence interactions [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. These involve multiple wave interactions, reflecting from surrounding boundaries and complex shock-shock, shock-vortex and shock-boundary layer interactions.…”
Section: Introductionmentioning
confidence: 99%